Lupus eritematoso crónico discoide hipertrófico simulando precursor de neoplasia de células escamosas [Chronic hypertrophic discoid lupus erythematosus mimicking sqamous-cell neoplasia] - Mercedes Lidia Hassan; Graciela Fátima Sanchez; Ignacio Luis Calb; José Gabriel Casas (Our Dermatology Online, 2016)
Introduction: Cutaneous Hypertrophic Lupus Erythematosus (CHLE) is a rare variant Of Chronic Discoid Lupus Erythematosus (CDLE) that is characterizated for the involvement of sites of the previous lesions, specially the face, with hyperkeratotic, elevated borders and crusted and erosive centers, refractories to therapy, that simulates epidermal neoplasias. The histopathological aspect was almost confusing due to the presence of atipias, loss of polarity of keratynocites, basal membrane interruption and heavy band of basal and dermic infiltrates of lymphocytes. Local treatment with potent corticosteroids was found it made up the involution of lesions, that had been presumed neoplastic in nature. Material and Methods: Clinical history,follow-up and outcome of a case. Results: We present a 69 year-old female patient with a 16 year-history of CDLE. After systemic treatment with cloroquine remained without cutaneous lesions until development of hypertrophic CDLE lesions in the previously affected skin. These lesions become worse with the use of tachrolimus topic and exhibited the aspect actinic keratosis-like in the three biopsies performed. Thereafter local Imiquimod induced its clinical tumoral aspect. Immunohistochemic with CD123 identificates some dendritic plasmocitoid cells in the upper dermis and dermoepidermal limit, althoug not too prominent. Only after the use of local high potency corticosteroid treatment the lesions were completely resolved and the patient remained asymptomatic for one year long, until present. Conclusion: The relevance of topic clobetasol response in the differential diagnosis of HCDLE vs actinic keratosis/squamous neoplasia, which made up the complete resolution of cutaneous lesions and avoid aggressive surgical behaviour.